2020
DOI: 10.3389/fmicb.2020.01845
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes and Specific Symbionts of Social Spiders: Compositional Patterns in Host Species, Populations, and Nests

Abstract: Social spiders have remarkably low species-wide genetic diversities, potentially increasing the relative importance of microbial symbionts for host fitness. Here we explore the bacterial microbiomes of three species of social Stegodyphus (S. dumicola, S. mimosarum, and S. sarasinorum), within and between populations, using 16S rRNA gene amplicon sequencing. The microbiomes of the three spider species were distinct but shared similarities in membership and structure. This included low overall diversity (Shannon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 69 publications
4
40
0
Order By: Relevance
“…The gut microbiome plays important roles in several spider traits, and recent studies have shown that spiders are hosts to many types of endosymbionts (Zhang et al, 2018b). Furthermore, it has been established that spiders on the same web are characterized by a very similar microbial richness, whereas differences in the microbial compositions are more pronounced among spiders on different webs (Busck et al, 2020). Kumar et al (2020) found that the gut microbiota in the Oxyopidae and Thomisidae spider families not only metabolize fatty acids and sugars but are also involved in the synthesis of vitamins.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome plays important roles in several spider traits, and recent studies have shown that spiders are hosts to many types of endosymbionts (Zhang et al, 2018b). Furthermore, it has been established that spiders on the same web are characterized by a very similar microbial richness, whereas differences in the microbial compositions are more pronounced among spiders on different webs (Busck et al, 2020). Kumar et al (2020) found that the gut microbiota in the Oxyopidae and Thomisidae spider families not only metabolize fatty acids and sugars but are also involved in the synthesis of vitamins.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation In total ve distinct morphotypes appeared on plates after 2-3 days, with milky-white, circular colonies as the dominant type. Cells of these colonies were Gram-positive cocci, 0.7 to 1.2 µm in diameter, non-motile and non-sporeforming, and occurred singly or in pairs; their partial 16S rRNA gene sequence represented an ASV found in 35% of all sequenced spiders of a previous study (Busck et al, 2020). was 100% identical to S. sciuri.…”
Section: Resultsmentioning
confidence: 84%
“…In a previous study, 16S rRNA gene amplicon sequencing of three social spider species revealed that the spider microbiomes were dominated by a few speci c endosymbionts but amplicon sequence variants (ASVs) indicative of spider surface microbes were also detected (Busck et al, 2020). We therefore aimed at isolating and characterizing putative symbiotic bacteria from the surface of social spiders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nest microbiomes of S. dumicola were shown to differ significantly between different sampling sites, even though there is a core microbiome on genus level ( Nazipi et al, 2021 ). A study investigating the spider microbiome of S. dumicola (endo- and exosymbionts) showed significant differences even between spiders from different nests from the same sampling site ( Busck et al, 2020 ). Therefore, differences of the nest and spider microbiomes between the different geographic sites might contribute to the differences between the volatilomes found in the present study.…”
Section: Discussionmentioning
confidence: 99%